2018
DOI: 10.4193/rhin18.016
|View full text |Cite
|
Sign up to set email alerts
|

Septoplasty for nasal obstruction due to a deviated nasal septum in adults: a systematic review

Abstract: Despite the routine application of septoplasty in clinical practice, the current body of evidence does not support firm conclusions on its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 29 publications
(69 reference statements)
1
62
0
9
Order By: Relevance
“…Treatment may consist of septoplasty or non‐surgical management. As the rationale behind septoplasty is to reduce symptoms of nasal obstruction rather than merely straightening the deviated septum, non‐surgical management is an equally suited alternative under current conditions of equipoise, which was confirmed by a recent systematic review . Surgical and non‐surgical management share the same target population (adults with nasal obstruction and a deviated septum) and intended effect (relieve of nasal complaints), and are considered suitable comparators …”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…Treatment may consist of septoplasty or non‐surgical management. As the rationale behind septoplasty is to reduce symptoms of nasal obstruction rather than merely straightening the deviated septum, non‐surgical management is an equally suited alternative under current conditions of equipoise, which was confirmed by a recent systematic review . Surgical and non‐surgical management share the same target population (adults with nasal obstruction and a deviated septum) and intended effect (relieve of nasal complaints), and are considered suitable comparators …”
Section: Methodsmentioning
confidence: 90%
“…Septoplasty, that is surgical correction of the deviated nasal septum, is an illustrative example within ENT‐practice. Although septoplasty is a common treatment for nasal obstruction, current literature on its effectiveness is scarce and inconclusive . The estimated prevalence of a deviated septum ranges up to 80%, whereas only a minority suffers from nasal obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of septoplasty with or without turbinate surgery remains unclear and there is a lack of high-quality evidence of its benefit in the literature [10,11]. Not all patients improve with surgery.…”
mentioning
confidence: 99%
“…Where septoplasty fails and further surgery becomes necessary, revision rates are reported to be high [14]. There is also a lack of robust evidence about the additional benefit of turbinate surgery [11]. One study showed reduced revision rates for septoplasty when the turbinate tissue is reduced [15]; other studies report no added long-term benefit from turbinate reduction [16][17][18].…”
mentioning
confidence: 99%
See 1 more Smart Citation